APLIKASI BERBAGAI DOSIS BOKASHI DAN UREA TERHADAP PERTUMBUHAN VEGETATIF BIBIT KOPI ROBUSTA - Basri Baba (Jurusan Budidaya Tanaman Perkebunan, Politeknik Pertanian Negeri Pangkajene Kepulauan, 2022)
This study aims to determine the vegetative growth of robusta coffee seedlings applied with bokashi and urea fertilizers. This research was conducted in Manggalung Village, Mandalle District, Pangkajene and Islands Regency, South Sulawesi Province, which took place from November 2020 to April 2021. This study was designed with a two-factor factorial randomized block design (RBD). The first factor is the dose of bokashi fertilizer (b) 3 levels: 0g (b0), 100 g (b1), and 150 g (b2) and the second factor is the dose of Urea (u): 0 g u0), 10 g (u1), and 15 g (u2). All data obtained in the study were analyzed by means of analysis of variance (ANOVA) followed by the Least Significant Difference (LSD) test with a level of accuracy (0.1 and 0.5). The results showed that with a dosage of 150 g / plant boca gave much better results and showed a very significant difference in plant height growth and number of leaves after the least significant difference (0.1%). Meanwhile, with the same dose of boca, namely 150 g (b2), it gave a good response to the increase in stem diameter. Therefore, the use of Boca fertilizer at a dose of 150 g gives good results on the vegetative growth of Robusta coffee seedlings.